2004
DOI: 10.1149/1.1803051
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Liquid Water Transport in a PEFC

Abstract: Using an optical H 2 /air polymer electrolyte fuel cell ͑PEFC͒, the mechanics of liquid water transport, starting from droplet emergence on the gas diffusion layer ͑GDL͒ surface, droplet growth and departure, to the two-phase flow in gas channels, is characterized under automotive conditions of 0.82 A/cm 2 , 70°C, and 2 atm. It is observed that water droplets emerge from the GDL surface under oversaturation of water vapor in the gas phase, appear only at preferential locations, and can grow to a size comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
263
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(271 citation statements)
references
References 5 publications
7
263
0
1
Order By: Relevance
“…Visualization method is an effective way to observe the two-phase flow, which has been used for tube [15] or minichannel [16] recently. Researchers have studied the two-phase flow caused by liquid water inside PEMFCs by using the direct visualization method and transparent PEMFCs [17][18][19][20][21][22][23][24][25][26][27]. Yang et al [19] applied an optical PEMFC to study the mechanics of liquid water transport.…”
Section: Introductionmentioning
confidence: 99%
“…Visualization method is an effective way to observe the two-phase flow, which has been used for tube [15] or minichannel [16] recently. Researchers have studied the two-phase flow caused by liquid water inside PEMFCs by using the direct visualization method and transparent PEMFCs [17][18][19][20][21][22][23][24][25][26][27]. Yang et al [19] applied an optical PEMFC to study the mechanics of liquid water transport.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical one-dimensional models for liquid water transport in gas diffusion layers (GDLs), where liquid water is controlled by capillary forces depending on the structure and wettability of GDL, have been reported [1,2], and three-dimensional simulations using two-phase models have been developed [3,4]. For liquid water transport in gas flow channels, experimental investigations have been conducted using transparent fuel cells and it was demonstrated that the surface tension of water and the wettability of the GDL and gas flow channel play a dominant role in the liquid water transport [5,6]. Some numerical simulations of the dynamic behavior of condensed water, which would be strongly affected by the wettability of GDL and gas flow channel, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…porous media | capillarity | wettability | microfluidics | pattern formation M ultiphase flow in porous media is important in many natural and industrial processes, including geologic CO 2 sequestration (1), enhanced oil recovery (2), water infiltration into soil (3), and transport in polymer electrolyte fuel cells (4). Much of the research on multiphase flow in porous media has focused on the effect of fluid properties and flow conditions.…”
mentioning
confidence: 99%